Pengaruh Ukuran Perusahaan, Solvabilitas, Ukuran Kap, Opini Auditor, Dan Tingkat Profitabilitas Terhadap Audit Delay (Studi Empiris Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia periode 2012-2014) SKRIPSI - Kusuma, Herfin (2016)
One of the qualitative characteristics of financial reporting is relevant, the manifestations can be seen from the Audit Delay. This study aimed to examine the effect of size of the company, solvability , size of the Public Accounting firm, auditor opinion, and profitability to Audit Delay on companies listed in Indonesia Stock Exchange. The sample used in this research are 277 companies listed in Indonesia Stock Exchange in 2012 until 2014. The sampling method using purposive sampling method. The analysis used in this study is a multiple linear regression analysis with a significance level of 5 percent, which is processed using the program Statistical Package for Social Science (SPSS) version 17. The results showed that the variable solvability, size of the Public Accounting and profitability effect on the Audit Delay, while the existence of an size of the company and the auditor opinion did not influence on the Audit Delay.